Analysis of Vegetation Changes Using Satellite Imagery and Normalized Difference Vegetation Index (NDVI): A Case Study in Tuntang District, Semarang District - Wirawan, Samuel Tommy Cadalora; Chernovita, Hanna Prillysca (Universitas Bina Darma, 2023)
Changes in land use from agriculture to residential and industry continue to occur in Tuntang District, and analysis is needed to identify areas experiencing the most significant changes. Development growth triggered by an increase in population can cause significant changes, such as the conversion of land from forests to agricultural land or plantations, as well as from agricultural land to residential and industrial areas. To monitor land changes, Remote Sensing is used as an effective tool. This method allows data analysis without direct contact with the object being studied. The use of Landsat-8 imagery, as a remote sensing tool, can help identify variations in vegetation. Analysis using the Normalized Difference Vegetation Index (NDVI) calculation method can provide information about the level of vegetation density in the area. The research results show significant changes in vegetation density in Tuntang District from 2019 to 2022. This change is believed to be related to the increase in population, which may be a driving force for several areas to experience development and changes in land function.